Nadzor nad nenadzorovanimi migracijami - Mlekuž, Jernej (Dve domovini, 2019)
The paper addresses how Slovenian newspapers reported on defections from Yugoslavia in the period from 1945-1965. During the time when departures from the SFRY were restricted and regulated, defections were sanctioned and the media were instrumentalized as a state ideological apparatus. It seems that defections were not a very common topic in the newspapers. When they did appear in newsprint, they were criminalized and not infrequently subjected to a fair amount of moralizing. When the defectors themselves were given voice, they expressed remorse and contrition, with the message that going abroad meant suffering, misery or even ruin.
Keywords: 1945-1965; authorities; časopisi; defections; discourse; diskurz; emigrants; izseljenci; Jugoslavija; jugoslovanski izseljenci; newspapers; oblast; poročanje medijev; prebegi; reporting in media; socialism; socializem; Yugoslav emigrants; Yugoslavia